Hyperkalaemia prevalence, recurrence and treatment in patients on haemodialysis in China: protocol for a prospective multicentre cohort study (PRECEDE-K). Issue 12 (22nd December 2021) - Ni, Zhaohui; Jin, Haijiao; Lu, Renhua; Zuo, Li; Yu, Weimin; Ren, Yuqing; Yang, Qiongqiong; Xiao, Jie; Zhang, Qinghong; Zhang, Lihong; Zhang, Xinzhou; Chen, Qinkai; et al.
Abstract : Introduction: Hyperkalaemia (HK) is a potentially life-threatening electrolyte imbalance associated with several adverse clinical outcomes and is common in patients with kidney failure. However, there is no evidence on the occurrence, recurrence and treatment of HK in patients on haemodialysis (HD) in China. Methods and analysis: The HK Prevalence, Recurrence, and Treatment in Haemodialysis Study is a prospective, multicentre, observational, cohort study being conducted across 15–18 sites in China. Approximately 600 patients with end-stage kidney disease on HD are anticipated to be enrolled and will be followed up for 24 weeks. Patients will be in the long interdialytic interval (LIDI) at enrolment and will receive follow-up care every 4 weeks in LIDI for pre-dialysis and post-dialysis (at enrolment only) serum potassium measurements. To obtain pre-dialysis serum potassium levels in the short interdialytic interval (SIDI), a follow-up visit will be performed in the SIDI during the first week. Information on concomitant medications, blood gas analysis and biochemistry measurements will be obtained at enrolment and at each follow-up visit. The primary endpoint will be the proportion of patients experiencing HK (defined as serum potassium level >5.0 mmol/L) at the study enrolment or during the 24-week follow-up. The key secondary endpoint will be the proportion of patients experiencing HK recurrence (defined as any HK event after the first HK event) within 1–6 months (if applicable) during the 24-week follow-up, including enrolment assessment. Ethics and dissemination: This study has been approved by Shanghai Jiaotong University School of Medicine, Renji Hospital Ethics Committee (2020-040). Other participating subcentres must also obtain ethics committee approval prior to the start of the study. The Good Clinical Practice regulations shall be strictly followed during the test implementation. Amendments to the protocol will be reviewed by the ethics committees. Written informed consent will be obtained from all participants before collection of any patient data and patient information. The findings of this study will be disseminated through peer-reviewed publications and conference presentations. Trial registration number: ClinicalTrials.gov Registry (NCT04799067 ).